Purchase Decisions For Bimoli Cooking Oil Products : The Influence of Celebrity Endorse, Brand Image and Brand Trust - Relifra Relifra; Ramadhi Ramadhi; Solandri Solandri (Jurnal Simki Economic, 2023)
Cooking oil is a basic need for Indonesian people without exception for the people of 4 villages in Sungai Liuk. Cooking oil is widely used in Indonesian food. One of the brands of cooking oil that is widely consumed is Bimoli. In this study to see the effect of celebrity endorsement, brand image and brand trust on purchasing decisions using multiple linear regression analysis with SPSS 24. The results of this study show that celebrity endorse, brand image and brand trust partially and simultaneously have a significant and positive effect on purchasing decisions for Bimoli cooking oil among consumers in 4 villages in the Sungai Liuk region.